Monitoring Information System to Ensure Completion of Medical Procedure Informed Consent Forms at Hospital X - Shinta Yuspita; Yuyun Yunengsih; Falaah Abdussalaam (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2025)
Medical action consent forms are known to be legal documents in the delivery of healthcare services. However, when they are not well completed, it affects the quality of services and the accountability of an institution. Recurring problems in documentation processes include incomplete data entry, late submissions, and substandard recording; all these increase risks for medical errors and administrative complications. A web-based information system was developed to address these systematic deficiencies using Rapid Application Development (RAD) methodology. Field observations and structured interviews with healthcare personnel were used as research tools in the design of this system. The development process continued through four iterative phases: requirements planning, user-centered design, system construction, and deployment evaluation. This platform comprises automated validation protocols that prevent incomplete submissions from being accepted into the database until all required fields have been completed by the user; real-time alert mechanisms for missing data fields within a submission; and streamlined interfaces optimized for clinical workflows. Functional testing shows statistically significant improvements in documentation efficiency and completion rates among medical staff documented by the system compared to those not documented by it. The system permits real-time documentation of procedures with lower error margins compared to existing methods plus shorter processing times than existing methods. This study found that RAD-based solutions present feasible approaches toward improving accuracy and speed in medical consent documentation while simultaneously achieving legal compliance and patient safety goals within hospitals. The platform uses technology-driven quality assurance mechanisms to solve longstanding challenges in documentation